Circular Economy Policy of Shrimp Waste as an Effort to Implement Green Economy - Suning Suning; Djoko Adi Walujo; Linda Dwi Rohmadiani; Prihono Prihono (Jurnal Kawistara, 2022)
This study aims at determining the conditions and characteristics of shrimp waste, the economic value of the potential for shrimp waste, as well as the policy direction for implementing the Circular Economy of Shrimp Waste as a Green Economy Alternative in the Bulak Banteng Kenjeran Coastal Area, Surabaya City. The research method used is descriptive qualitative and quantitative with the process hierarchy analysis technique (AHP). The data collection method was carried out by distributing questionnaires and in-depth interviews with selected respondents. The results showed that the characteristics of shrimp waste in the form of shrimp heads and shells were still not used for economic value activities, and people dumped them in gutters around homes and at sea. The priority policy directions that can be applied to the Circular Economy of Shrimp Waste as an Alternative to a Green Economy are; 1) providing innovation and technology for economic-based shrimp waste processing with a total CR (consistency ratio) value of 1.878; 2) to improve environmental health by not disposing of shrimp waste around the house, the total value of CR is 1.127; and, 3) the government provides a shrimp processing industry for fishermen with a total CR value of 0.094. Each policy priority can be carried out in synergy so that shrimp waste can be handled properly.